Aflatoxin B1-Adsorbing Capability of Pleurotus eryngii Mycelium: Efficiency and Modeling of the Process - Haidukowski, Miriam; Casamassima, Eliana; Cimmarusti, Maria Teresa; Branà, Maria Teresa; Longobardi, Francesco; Acquafredda, Pasquale; Logrieco, Antonio; Altomare, Claudio (Frontiers in Microbiology, 2019)
Aflatoxin B1 (AfB1) is a carcinogenic mycotoxin that contaminates food and feed worldwide. We determined the AfB1-adsorption capability of non-viable Pleurotus eryngii mycelium, an edible fungus, as a potential means for removal of AfB1 from contaminated solutions. Lyophilized mycelium was produced and made enzymatically inert by sterilization at high temperatures. The material thus obtained was characterized by scanning electron microscopy with regard to the morpho-structural properties of the mycotoxin-adsorbing surfaces. The active surfaces appeared rough and sponge-like. The AfB1-mycelium system reached equilibrium at 37°C, 30 min, and pH 5–7, conditions that are compatible with the gastro-intestinal system of animals. The system remained stable for 48 h at room temperature, at pH 3, pH 7, and pH 7.4. A thermodynamic study of the process showed that this is a spontaneous and physical adsorption process, with a maximum of 85 ± 13% of removal efficiency of AfB1 by P. eryngii mycelium. These results suggest that biosorbent materials obtained from the mycelium of the mushroom P. eryngii could be used as a low-cost and effective feed additive for AfB1 detoxification.